Persepsi Pedagang Terhadap Komunikasi Persuasif dalam Program Relokasi Pasar Anyar Tangerang - permadi, muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2025)
This study examines the persuasive communication strategies implemented in the relocation program of Pasar Anyar Tangerang, focusing on merchants' perceptions of the communication process. Using a qualitative descriptive approach, this research involved in-depth interviews with three merchants who experienced relocation to Mall Metropolis and Pasar Mambo. The findings reveal that the effectiveness of persuasive communication is influenced by several key factors such as information consistency, process transparency, relocation site selection, and financial considerations. Although management has implemented a dialogical approach through deliberation and intensive coordination, challenges were still found in the form of information inconsistency and changing decisions. Relocation site factors and operational costs became the main considerations for merchants in accepting or rejecting the relocation program.